A comprehensive analytical model for global buckling analysis of general grid cylindrical structures with various cell geometries. Issue 6 (2nd November 2021) - Abbasi, Mahdi; Ghanbari, Jaafar
Abstract: In this paper, we present an analytical method based on equivalent continuum homogenization for the global buckling analysis of the general grid lattice cylindrical structures. In the proposed scheme, grid structures with arbitrary cell geometries can be analyzed by obtaining their effective cell stiffness based on force and moment analysis of the struts. The grid structures are assumed to be composed of curvilinear axial, circumferential, and oblique unidirectional composite ribs. To evaluate the results of the presented analytical method, a parametric finite element code is derived to generate the desired geometry of the grid structures and their buckling loads are obtained and compared with the analytical method. The effects of various parameters, including the number of ribs, their thickness and elastic properties, and helical angle of the oblique ribs are studied for hexagonal, triangular, and mixed grid shells. The results are compared with the available data published in the literature with a good agreement.